Secure authentication schemes in cloud computing with glimpse of artificial neural networks: A review - Syed Amma Sheik; Amutha Prabakar Muniyandi (Cyber Security and Applications)
The fast growth of the cloud computing technology has led to immense development in the public and private sectors. Cloud computing provides a high level of virtualization, massive scalability, multitenancy and elasticity. This has enabled organizations, academia, government departments and the public to move forward with this technology. However, they are unable to assuredly place their information over the clouds due to many security threats. Cloud security plays a vital role to establish a confidence between the cloud service providers, consumers and the multi-users to maintain the security levels of their data. This paper focuses the survey for cloud security issues, existing authentication schemes, data storage technologies and offers a glimpse of Artificial Neural Networks (ANNs) applied to the cloud security.